Coronary sinus iatrogenic lesion during repeated mitral valve replacement: case report of an immediate transmitral annulus repair - Evora,Paulo R. B. (2003)
We report a case and evolution of a patient in whom the coronary sinus was damaged and reconstructed through the mitral annulus. The surgical accident happened during a degenerated biological valve prosthesis instrumentation. An almost complete left circumflex coronary artery division was our first hypothesis. A coronary probe introduced through the vascular injury was distally detected inside the right atrium confirming a coronary sinus lesion. The surgical correction was performed using running polypropylene 7-0 sutures through the mitral ring. After fourteen months, a coronary sinus angiographic image was taking observing the venous phase of selective left coronary arteriography. The image demonstrated an acceptable narrowing of the local venous repair. In our opinion the single coronary sinus division or its repair, in this iatrogenic situation, is a matter of speculation.